Let’s sp(l)ice up pluripotency! - Martello, Graziano (European Molecular Biology Organization, 2013)
NCB (2013) 15: 1141–1152 ; DOI: 10.1038/ncb2839; published online 09 08 2013 mRNA-splicing presents an important regulatory step that contributes to the functional repertoire of all cell types and tissues. Profound changes in alternative splicing have also been revealed during embryonic stem cell (ESC) differentiation. Based on a genome-wide screen for pluripotency regulators, Ng and colleagues now identify SON as a new splicing regulator in the maintenance of human ESC pluripotency and self-renewal (Lu et al, 2013).